Model Prediksi Tipe Komentar Di Instagram Terkait Pemilu 2024 Menggunakan Metode Winnowing - Rahmani, Budi; Sejati, Noor (STMIK Banjarbaru, 2024)
This study addresses the challenges of sentiment analysis for social media comments related to the 2024 Presidential Election on Instagram, where the high volume of discussions can influence public opinion and political participation. The main issue is the inaccuracy in sentiment classification (positive, negative, neutral) and the need to filter irrelevant comments. We propose using the Winnowing Algorithm, which effectively detects text similarity with high accuracy for automatic sentiment classification. The methodology includes collecting comment data, text preprocessing, and applying the Winnowing Algorithm. Experimental results demonstrate high accuracy (F1-score > 85%) in sentiment identification and filtering of irrelevant comments. These findings contribute to developing automatic sentiment analysis systems on social media and enhancing public opinion management in the digital political realm. This research also has implications for developing more responsive and scalable sentiment prediction systems.Keywords: Prediction; Sentiment analysis; Instagram; 2024 Presidential Electio; Winnowing AlgorithmÂ AbstrakPenelitian ini mengkaji tantangan analisis sentimen komentar media sosial terkait Pemilu Presiden 2024 di Instagram, di mana volume diskusi yang tinggi dapat memengaruhi opini publik dan partisipasi politik. Masalah utama adalah ketidakakuratan dalam klasifikasi sentimen (positif, negatif, netral) dan penyaringan komentar yang tidak relevan. Untuk itu, kami mengusulkan penerapan Algoritme Winnowing, yang efektif dalam mendeteksi kesamaan teks dengan akurasi tinggi, guna klasifikasi sentimen otomatis. Metodologi meliputi pengumpulan data komentar, pra-pemrosesan teks, dan penerapan Algoritme Winnowing. Hasil eksperimen menunjukkan akurasi tinggi (F1-score > 85%) dalam identifikasi sentimen dan penyaringan komentar tidak relevan. Temuan ini memberikan kontribusi pada pengembangan sistem analisis sentimen otomatis di media sosial dan peningkatan pengelolaan opini publik di ranah politik digital. Penelitian ini juga berimplikasi pada pengembangan sistem prediksi sentimen yang lebih responsif dan scalable.Â